Evolution of casein kinase 1 and functional analysis of new doubletime mutants in Drosophila - Thakkar, Nirav; Giesecke, Astrid; Bazalova, Olga; Martinek, Jan; Smykal, Vlastimil; Stanewsky, Ralf; Dolezel, David (Frontiers in Physiology, 2022)
Circadian clocks are timing devices that rhythmically adjust organism's behavior, physiology, and metabolism to the 24-h day-night cycle. Eukaryotic circadian clocks rely on several interlocked transcription-translation feedback loops, where protein stability is the key part of the delay between transcription and the appearance of the mature proteins within the feedback loops. In bilaterian animals, including mammals and insects, the circadian clock depends on a homologous set of proteins. Despite mostly conserved clock components among the fruit fly Drosophila and mammals, several lineage-specific differences exist. Here we have systematically explored the evolution and sequence variability of insect DBT proteins and their vertebrate homologs casein kinase 1 delta (CKIδ) and epsilon (CKIε), dated the origin and separation of CKIδ from CKIε, and identified at least three additional independent duplications of the CKIδ/ε gene in Petromyzon, Danio, and Xenopus. We determined conserved regions in DBT specific to Diptera, and functionally tested a subset of those in D. melanogaster. Replacement of Lysine K224 with acidic residues strongly impacts the free running period even in heterozygous flies, whereas homozygous mutants are not viable. K224D mutants have a temperature compensation defect with longer free-running periods at higher temperatures, which is exactly the opposite trend of what was reported for corresponding mammalian mutants. All DBTs of dipteran insects contain the NKRQK motif at positions 220-224. The occurrence of this motif perfectly correlates with the presence of BRIDE OF DOUBLETIME, BDBT, in Diptera. BDBT is a noncanonical FK506-binding protein that physically interacts with Drosophila DBT. The phylogeny of FK506-binding proteins suggests that BDBT is either absent, or highly modified in non-dipteran insects. In addition to in silico analysis of DBT/CKIδ/ε evolution and diversity, we have identified four novel casein kinase 1 genes specific to the Drosophila genus.